Locomotor kinematics of tree squirrels (Sciurus carolinensis) in free‐ranging and laboratory environments: Implications for primate locomotion and evolution. Issue 2 (18th October 2018) - Dunham, Noah T.; McNamara, Allison; Shapiro, Liza; Phelps, Taylor; Wolfe, Adrienne N.; Young, Jesse W.
Abstract: The grasping capabilities and gait kinematics characteristic of primates are often argued to be adaptations for safely moving on small terminal branches. The goal of this study was to identify whether Eastern gray squirrels ( Sciurus carolinensis )—arboreal rodents that frequently move and forage on small branches, lack primate‐like grasping and gait patterns, and arguably represent extant analogs of a stem primate ancestor—adjust gait kinematics to narrow and nonhorizontal branches. We studied locomotor kinematics of free‐ranging and laboratory‐housed squirrels moving over various substrates. We used high‐speed video to film (a) a population of free‐ranging squirrels moving on natural substrates and (b) laboratory‐housed squirrels moving on horizontal poles. Substrates were coded as small, medium, or large relative to squirrel trunk diameter, and as inclined, declined, or horizontal. Free‐ranging squirrels used more gallops and half‐bounds on small‐ and medium‐sized substrates, and more high‐impact bounds, with reduced limb‐lead durations, on declined substrates. Laboratory squirrels moved at higher speeds than free‐ranging squirrels and responded to decreasing diameter by using more gallops and half‐bounds, lowering speed, and—controlling for speed—increasing mean duty factor, mean number of supporting limbs, and relative forelimb lead duration. Our inability to detect substantial diameter or orientation‐related gait adjustments in the wild may be due to a limited accounting of confounding influences (e.g., substrate compliance). Ultimately, studies assessing stability measures (e.g., center of mass fluctuations and peak vertical force) are required to assess whether primates' enhanced grasping and gait patterns engender performance advantages on narrow or oblique substrates. Abstract : We examined the locomotor kinematics of free‐ranging and laboratory‐housed Sciurus carolinensis in response to changes in substrate diameter and orientation. A similar pattern emerged across both recording environments: squirrels tended to adjust gait type in response to narrowing substrate diameter (i.e., more gallops and half‐bounds on small substrates). Under laboratory conditions, squirrels displayed additional gait adjustments thought to promote stability on narrower substrates, and free‐ranging squirrels adjusted gait‐type and limb‐lead durations in response to declining substrates.